BIOMASS PRODUCTION AND SINGLE-CELL PROTEIN (SCP) ENCAPSULATION OF BACTERIA Bacillus cereus SN7 - Mukramin, Ibnu; Feliatra, Feliatra; Tanjung, Afrizal (Asian Journal of Aquatic Sciences, 2024)
Bacillus cereus SN7 is a bacterium with potential applications in producing Single-Cell Protein (SCP). SCP can be an alternative to protein derived from traditional sources like agriculture, fisheries, and animal husbandry. Encapsulation is a process used to stabilize cells, aiming to potentially enhance probiotics' viability and stability throughout production, storage, and handling. This study aims to make capsules from B. cereus SN7 single-cell protein to protect them from contaminants. This study used a survey method, which carried out in-situ processing of bacteria, as well as conducting experiments on the formation of bacterial encapsulation, testing the effectiveness of encapsulation, and observing the viability of B. cereus SN7 bacteria by counting the number of colonies. B. cereus produced biomass with a total dry weight of 1.3708 g/mL. The alginate encapsulation experiments can be formed into capsule beads that protect bacteria. The best encapsulation process is an alginate-based coating, which is indicated by the ability of the alginate to withstand temperature, pH, and salinity.